Valores e educação na história e no imaginário de oito professores de São Paulo - Hoyler, Sandra Helena Loureiro (2009)
The aim of this paper was to research the thoughts of classical and contemporary authors, as well as teachers in the city of São Paulo, concerning values. Our starting point was the highlight given by Terezinha Rios to four fundamental values: dialogue, respect, justice and solidarity, which are essential and meaningful in a teacher s life. Firstly, we read texts dating the ancient times, written by Homero and Hesíodo, in order to understand the origin of the word areté, later known as virtue. Secondly, we read texts belonging to Classical Greece written by the sophists Socrates, Plato and Aristotle. Then, we read texts belonging to Middle Age, written by Saint Agostin and Tomas de Aquino. From modernity, we read texts written by Martinho Lutero and Inácio Loyola and, from the 17th century, we read Coménio. From the 18th and 19th centuries, we studied Rousseau and Durkheim. In all of them, we paid attention to the values that they defended and spreaded. From the contemporary age, we tried to understand, by reading Josep Maria Puig, specialist in moral education, what values are and how they are built. We also summarized some of the reflections made by Paolo Nosella and Terezinha Rios about ethics and values in teaching. This preliminary study intends to make us theoretically sensitive in order to discover if the values mentioned by Terezinha Rios are still defended by teachers in classrooms in São Paulo. We checked this by means of surveys, which were applied to a certain number of teachers. This brief exploratory study and the long historic period which was taken into consideration enabled us to conclude that, although the values which are practiced nowadays when it comes to teaching are the same from the past, their characterization and importance vary, sometimes in a deep way, according to the political-economical moment.